1994
DOI: 10.1017/s0022050700015072
|View full text |Cite
|
Sign up to set email alerts
|

The Shoe That Didn't Drop: Explaining Banking Stability During the Great Depression

Abstract: This article attempts to account for the exceptional stability exhibited by the banking systems of Britain, Canada, and ten other countries during the Great Depression. It considers three possible explanations of stability—the structure of the commercial banking system, macroeconomic policy and performance, and lender of last resort behavior—employing data from 25 countries across Europe and North America. The results suggest that macroeconomic policy—especially exchange-rate policy—and banking structure, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
100
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(103 citation statements)
references
References 9 publications
3
100
0
Order By: Relevance
“…Schnabel and Shin (2004) found twin crises in 1763, and della Paolera and Taylor (2001) analyzed the 1890 Baring Crisis in Argentina as a twin crisis, suggesting that the Kaminsky and Reinhart story has simple historical applicability. Grossman (1994), however, found quite a different result in the interwar period. He found that the only predictor of a banking crisis in this period was whether a country was on the gold standard.…”
Section: Crises In Generalmentioning
confidence: 85%
See 1 more Smart Citation
“…Schnabel and Shin (2004) found twin crises in 1763, and della Paolera and Taylor (2001) analyzed the 1890 Baring Crisis in Argentina as a twin crisis, suggesting that the Kaminsky and Reinhart story has simple historical applicability. Grossman (1994), however, found quite a different result in the interwar period. He found that the only predictor of a banking crisis in this period was whether a country was on the gold standard.…”
Section: Crises In Generalmentioning
confidence: 85%
“…This correlation of bank troubles and exchange rate regimes is not affected by the structure of banking in different countries. It was the gold standard, not the structure of banking, that made banks vulnerable in the Great Depression (Grossman 1994).…”
Section: More Recent Analysesmentioning
confidence: 99%
“…As has been widely noted by economic historians, the financial crisis of the 1930s manifested itself as twin crises in many countries (Grossman, 1994;Grossman and Meissner, 2010). With capital controls in place, however, these countries could now conduct monetary policy with the aim of injecting liquidity into banking systems.…”
Section: B Further Evidence On Monetary Policymentioning
confidence: 99%
“…See Grossman (1993) for a more detailed and generally complementary analysis of the causes of interwar banking panics.…”
Section: Deflation and The Financial Systemmentioning
confidence: 99%